USULAN PENERAPAN METODE SIX SIGMA UNTUK MENGURANGI TINGKAT KECACATAN PADA PROSES PRODUKSI PIPA API 14 INCH DI PT BAKRIE PIPE INDUSTRIES - Khaedir Khaedir; wawan Kurniawan (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
PT. Bakrie Pipe Industries is a company engaged in the production of steel pipe. Pipe -steel pipe produced by PT. Bakrie Pipe Industries is used for a variety of needs such as: pipes foroil and gas , for the installation of water pipes, pipes for construction purposes, and for otherpurposes. PT. Bakrie Pipe Industries always maintain the quality of the resulting production andefforts to minimize the failure existing production of the company's. Therefore, Do research usingthe six sigma method with methodology DMAIC (Define, Measure, Analyze, Improve, andContorol) expected by using this method can minimize the defects and also improve the speed ofproduction.In the define stage, the selection of products to research the specs API steel pipe with14-inch size that has defects percentage of 5.25% and therefore this product the focus ofresearch.Furthermore the Measure stage is measurement sigma level company, the results of thesemeasurements show the value of 26,285 DPMO with sigma level was 3.44 sigma that indicates thatvalue still far from the target of 6 sigma.The next stage is a Analayze stage to analyze the causesof production failure that occurred in production, using Ishikawa diagram and FMEA tables.Thenthe Improve stage is giving suggestions for improvement and suggestions given for companay with:the application of methods of DOE (Design Of Experiments) with factorial 21 to find the optimaldistance in screw machine, giving proposed a tool is Roll Waterpass and application formmonitoring for the surveillance for removing the beads process. After do some implementationsgained increasing value 21,662 DPMO and sigma value of 3.52 sigma.